Magnitude and factors associated with adherence to Iron-folic acid supplementation among pregnant women in Eritrean refugee camps, northern Ethiopia - Mekdemariam Getachew; Mebrahtu Abay; Hiwet Zelalem; Tirhas Gebremedhin; Teklit Grum; Alemayehu Bayray (BMC, 2018)
Abstract Background Globally, anemia is a public health problem affecting the life of more than two billion people. Pregnant women are at high risk of iron deficiency anemia due to increased nutrient requirement during pregnancy. Iron-folic acid supplementation is the main strategy for prevention and control of iron deficiency anemia and its effectiveness depends on adherence to Iron-Folic Acid tablets. In the refugee camps of Ethiopia, despite the efforts made to reduce iron deficiency anemia during pregnancy, information about adherence to iron-folic acid supplementation and its associated factors are lacking. The objective of this study was to assess magnitude and factors associated with adherence to iron-folic acid supplementation, among pregnant women, in Shire refugee camps. Methods Institution based cross-sectional study with mixed design (quantitative and qualitative) was carried out among pregnant women in Shire refugee camps from September to November 2015. For quantitative data, a sample of 320 pregnant women was systematically selected and data were collected via interview administered structured questionnaire. Quantitative data were coded and entered into Epi-info version 3.5.1 and exported into a statistical package for social sciences (SPSS) Version 19.0 software for analysis. Bivariable and multivariable logistic regressions were employed to identify the predictors at p-value < 0.2 and 0.05 respectively. For the qualitative part, six focus group discussions and three key informant interviews were conducted on purposely-selected individuals. Open-Code version 3.6.2.0 was used for analysis. Identified themes were arranged into coherent groupings and triangulated with quantitative findings. Results The adherence rate was found to be 64.7% [95% CI (59.7%, 70.0%)]. Women who were having lower knowledge about anemia [AOR; 0.23 95% CI (0.14, 0.38)] and not receiving information about importance of iron-folic acid supplementation [AOR; 0.43 95% CI (0.25, 0.74)] were negatively associated with adherence to iron and folic acid., Having four or more antenatal care visits [AOR; 2.83 95% CI (1.46, 5.48)] were positively significantly associated with adherence to iron-folic acid supplementation. Conclusions Adherence rate of iron-folic acid supplementation during pregnancy in the study area is relatively low. Proper counseling and health promotion about Iron-Folic Acid tablet intake, promoting the benefits of early and frequent ANC visit, health promotion on anemia prevention and health benefits of the importance of iron-folic acid supplements are recommended to increase adherence with iron-folic acid supplementation.